If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -42 = -10 Reorder the terms: -42 + x = -10 Solving -42 + x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + x = -10 + 42 Combine like terms: -42 + 42 = 0 0 + x = -10 + 42 x = -10 + 42 Combine like terms: -10 + 42 = 32 x = 32 Simplifying x = 32
| X-24=28+3x | | 175m-125m+43425=45000-175m | | -8x-9(-19)=11 | | 9/2/9-4/-1/2 | | 16/13p-9p | | -22x-6=39 | | 2x=360-120 | | -5-8+-5j-1-7= | | 4(5+6x)=20 | | 1/4*5/3 | | 2x+55=90 | | 3x+32=25 | | 10x-151=89+2x | | 3(I+1)=5(I-3) | | 2x=360-200 | | x+82=-16 | | -8-x=8 | | 19=10-5w+9w-7 | | 6x(21-7)/21 | | 4.9b=107.8 | | -14k-11=40k | | 2.8(10.3+-7.6h)+-7.1= | | X^2+64-16x-z^2=0 | | Y=-2000X+25000 | | -13-13=x | | -10(8)-8y=-8 | | 3x-4x=6+3x | | 7/8•(-8/9) | | 4+(-25)=x | | 6(4x+5)=198 | | x/36=8. | | -56+9x=118+3x |